Peran Unit Usaha Pesantren dalam Mengembangkan Jiwa Kewirausahaan - Octaviani Octaviani; Esha Aulia; Shofwatul Fuadah; Mita Nasywa; Ferida R (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic boarding schools (pesantren) as traditional Islamic educational institutions not only serve as places for shaping students’ character, morals, and spirituality but also hold great potential in developing community economic independence through the management of pesantren business units. These business units are a concrete manifestation of the values of independence, hard work, and responsibility taught in the pesantren’s educational process. The purpose of this study is to examine in depth the role of pesantren business units in supporting the economic self-reliance of the pesantren itself as well as their contribution to empowering the surrounding community. This study employs a descriptive qualitative method with a case study approach on several pesantren that have successfully developed various business units such as cooperatives, agriculture, livestock, garment production, and student shops. The results show that pesantren business units function not only as a means of entrepreneurship education for students but also as a primary source of funding to support the operational activities of the pesantren. In addition, they act as the driving force of the local economy by creating employment opportunities, increasing income, and promoting community-based economic empowerment. The success of pesantren business units is influenced by professional management, strong leadership support, and the ability to innovate and adapt to changing times.